PERANCANGAN DAN VALIDASI MODUL PENYUSUN SERIOUS GAME BERBASIS SEPEDA VIRTUAL UNTUK REHABILITASI PASCA STROKE - Muh. Fuad Al Haris; Eka Mistiko Rini (Jurnal Teknologi Informasi dan Terapan, 2019)
In this research we present the modules of virtual reality augmented cycling (VRAC) system for people post stroke including mechatronic rehabilitation system and virtual environment. VRAC modules are designed as modular system to suit most stationary bicycles in virtual reality (VR) cycles without changing its parts. VRAC consists of novel hardware components embedded with sensors that are use to gain of a stationary exercise bicycle. VRAC modules include balancing pedals module, rpm (rotation per minute) counter module, safety driving module , handlebar module and acquisition data module. The handle system is a novel type of hand dynamometer, which measures applied physical force to control dynamic motion of the rider in the virtual environment. The data from sensing systems are measured by Arduino microcontroller as a acquisition data module and sent its results to virtual environment processed by computer. The prototype of the system was successful in demonstrating that a modular mechatronic kit can monitor and record kinetic, kinematic and physiologic parameters of riders.